2012
DOI: 10.1248/bpb.35.151
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Inhibition between Carvedilol Enantiomers during Racemate Glucuronidation Mediated by Human Liver and Intestinal Microsomes

Abstract: Carvedilol is administered orally as a racemic mixture of R( )-and S( )-enantiomers for treatment of angina pectoris, hypertension and chronic heart failure. We have reported that enzyme kinetic parameters for carvedilol glucuronidation by human liver microsomes (HLM) differed greatly depending on the substrate form, namely, racemic carvedilol and each enantiomer. These phenomena were thought to be caused by mutual inhibition between carvedilol enantiomers during racemate glucuronidation. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…In healthy adults, glucuronidation accounts for 20-23% of total carvedilol CL (Neugebauer and Neubert, 1991) and three UGT isoforms, UGT1A1, UGT2B4, and UGT2B7, are involved in its metabolism (Ohno et al, 2004). The contributions of UGT1A1, UGT2B4, and UGT2B7 are reported to be about 30%, 25-40%, and 30-45% for R-carvedilol, and 12-20%, 15-26%, and 60-65% for S-carvedilol, respectively (Takekuma et al, 2012).…”
Section: Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy adults, glucuronidation accounts for 20-23% of total carvedilol CL (Neugebauer and Neubert, 1991) and three UGT isoforms, UGT1A1, UGT2B4, and UGT2B7, are involved in its metabolism (Ohno et al, 2004). The contributions of UGT1A1, UGT2B4, and UGT2B7 are reported to be about 30%, 25-40%, and 30-45% for R-carvedilol, and 12-20%, 15-26%, and 60-65% for S-carvedilol, respectively (Takekuma et al, 2012).…”
Section: Eliminationmentioning
confidence: 99%
“…Carvedilol is a racemic mixture of two enantiomers, with S-enantiomer having both a 1 -receptor-blocking and b-adrenoreceptor-blocking activities, whereas R-enantiomer is more selective toward a 1 -receptor-blocking activity (Neugebauer et al, 1990). Both enantiomers undergo extensive stereoselective first-pass metabolism through CYP enzymes (CYP2D6, CYP1A2, CYP2C9, CYP3A4, and CYP2E1) and UGT enzymes (UGT1A1, UGT2B4, and UGT2B7) (Oldham and Clarke, 1997;Ohno et al, 2004;Takekuma et al, 2012), with reported absolute bioavailability (F) of 31.1% for R-carvedilol and 15.1% for S-carvedilol (Neugebauer et al, 1990). Because CYP2D6 is the main metabolic enzyme that is involved in the metabolism of both enantiomers and is more selective toward the overall disposition of R-carvedilol, the decrease activity of this enzyme in poor metabolizers (PMs) may result in higher systemic concentration of R-carvedilol and hence an increase in a-blockade, which can cause acute blood pressure reduction and increased incidence of orthostatic hypotension in comparison with extensive metabolizers (EMs) of CYP2D6 (Zhou and Wood, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…2A). Takekuma et al 16) reported that the stereoselectivity for R-and S-carvedilol glucuronidation estimated in HLM differed greatly depending on the substrate form, namely racemic carvedilol and each enantiomer. This phenomenon is thought to be caused by mutual inhibition between carvedilol enantiomers during racemate glucuronidation.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is thought to be caused by mutual inhibition between carvedilol enantiomers during racemate glucuronidation. 16) Therefore, to understand simply why amiodarone stimulates glucuronidation for R-carvedilol, rather than S-carvedilol, we compared the effects of amiodarone on the glucuronidation of each enantiomer separately (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the overall cardioprotective action of S(-)-Carvedilol is more and hepatotoxicity is less when compared to that of racemic and R(+)-Carvedilol [6]. In most of the cases, racemic mixtures are more preferred for oral administration than those of the enantiomer because of high cost and difficulty in selective synthesis of one optical isomer [7]. Hence there is a need to develop a validated method for the analysis of S(-)-Carvedilol from API and marketed formulations.…”
Section: Introductionmentioning
confidence: 99%